Consolidation of Proceedings in Brazilian Publicly Listed Corporations' Arbitration (Global Journal of Human-Social Science, 2024)
The objective of this Article is to demonstrate how arbitration proceedings involving publicly listed corporations, multiple shareholders, and consolidation of proceedings are being processed in Brazil. Some listed companies in Brazil are required to submit to arbitration all corporate disputes, and there is no procedural rule set forth by law or by the rules of some of the arbitration chambers in Brazil on how to consolidate similar proceedings initiated by different parties on the same issues, and how to decide on the jurisdiction of the arbitral tribunals. This issue has since been discussed by scholars, legislators, and arbitration chambers, that propose different solutions, and has recently been ruled by The Brazilian Superior Court of Justice. Within this context, a deductive approach will be applied to the Article, with bibliographic and case-law research.
Keywords: brazil; arbitration; publicly listed companies; shareholders; corporate disputes; consolidation of arbitrations